Collaboration among stakeholders key to the organic agriculture movement in Negros Occidental - Gasmen, Andrew D., Baconguis, Rowena DT (The Journal of Public Affairs and Development, 2015)
The organic agriculture movement in Negros Occidental can be traced back in the 1970s through the advocacy of the civil society. The movement received significant push when the local government issued policies and formulated programs that supported organic agriculture, and further, when the private sector supported the marketing of the produce. This paper explores collaboration among organic practitioners, government agencies, and the private sector as well as their interactions that significantly advanced organic agriculture. The research is an intrinsic case study as it investigate organic agriculture through in-depth data collection involving multiple sources of information. Results show patterns of interaction as evidenced by established networks and collaborative arrangements among organic practitioners - as individuals and organized groups - as well as interaction among agencies and institutions - public and private - that provide support services. Pressing needs for inputs, technical support and market drew organic practitioners together to interact. Organic policies and programs, organic certification and market support, among others, were integral in bringing together support agencies and other stakeholders, which created opportunities for collaboration. Despite active collaboration, full development of the organic sector remains elusive. A model is proposed to maximize local market potentials through partnership between big and small farmers.